2003
DOI: 10.1097/01.ju.0000075055.34506.59
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in the Cardiac Patient: How Common and Should We Treat?

Abstract: ED is extremely common in men with chronic coronary artery disease (affecting approximately 75%) yet most cardiologists do not ask about it. The SHIM is a useful, quick and inexpensive tool for discussion and diagnosis of ED in this population. Although it is well established that cardiovascular risk factors are associated with erectile dysfunction, once it is present there is mixed information on whether treating the risk factors will treat the ED. Problems appear to be that lifestyle modification in midlife … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
1
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(164 citation statements)
references
References 21 publications
5
151
1
7
Order By: Relevance
“…21,22 In 2003, a pathophysiological mechanism, the 'artery-size hypothesis,' was proposed by Montorsi et al to explain the link among ED, CAD, and stroke. 23 Atherosclerosis, a systemic disorder, should theoretically affect all the major vascular beds simultaneously, and to the same extent. However, the involvement of multiple vessels is rarely clinically evident at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In 2003, a pathophysiological mechanism, the 'artery-size hypothesis,' was proposed by Montorsi et al to explain the link among ED, CAD, and stroke. 23 Atherosclerosis, a systemic disorder, should theoretically affect all the major vascular beds simultaneously, and to the same extent. However, the involvement of multiple vessels is rarely clinically evident at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…17 Questions 1-5 and 15 of the IIEF constitute the erectile function domain, which is used to assess global erectile function. Scoring the IIEF domain of erectile function allowed the classification of each patient as follows: absent of ED (26)(27)(28)(29)(30), mild ED (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate ED (11)(12)(13)(14)(15)(16) and severe ED (0-10).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of ED is directly influenced by age, number of risk factors, and presence of cardiovascular disease [2,3]. Moreover, high prevalence of ED has been reported in conjunction with vascular abnormalities, such as coronary artery disease (CAD) [4][5][6], hypertension [7], cerebrovascular disease [8], and peripheral arterial disease [9]. Despite these studies suggesting that ED should be classified as a vascular disease, little is known about potential mechanism(s) by which ED and CAD may be associated.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Interestingly, cardiovascular disorders including coronary artery disease closely correlate with the incidence of ED in patients with vascular risk factors. 4,5 Epidemiologic studies have shown that nearly 75% of men with coronary artery disease also suffer from ED. 4,5 One explanation may be that vascular and cavernosal smooth muscle and endothelial cell dysfunction share the same risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Epidemiologic studies have shown that nearly 75% of men with coronary artery disease also suffer from ED. 4,5 One explanation may be that vascular and cavernosal smooth muscle and endothelial cell dysfunction share the same risk factors.…”
Section: Introductionmentioning
confidence: 99%